2020
DOI: 10.1111/1749-4877.12501
|View full text |Cite
|
Sign up to set email alerts
|

Diel differences in blue whale (Balaenoptera musculus) dive behavior increase nighttime risk of ship strikes in northern Chilean Patagonia

Abstract: The northern Chilean Patagonia region is a key feeding ground and a nursing habitat in the southern hemisphere for blue whales (Balaenoptera musculus). From 2014 to 2019, during 6 separate research cruises, the dive behavior of 28 individual blue whales was investigated using bio-logging tags (DTAGs), generating ≈190 h of data. Whales dove to significantly greater depths during the day compared to nighttime (day: 32.6 ± 18.7 m; night: 6.2 ± 2.7 m; P < 0.01). During the night, most time was spent close to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…They extend across ecological timescales, from the cycles of the tides (Gibson 2003;Krumme 2009) to those of the seasons (Hyndes et al 1999;Milligan et al 2020) and those exhibited over ontogenetic development (Grubbs 2010;Frank et al 2018). They are also prevalent across trophic levels, from the diel vertical migration (DVM) of plankton (Hays 2003;Bianchi and Mislan 2016) to the diving patterns of cetaceans (Keen et al 2019;Caruso et al 2020) and pelagic sharks (Papastamatiou and Lowe 2012;Schlaff et al 2014). An important area of research in marine ecology is to understand the drivers of these trends.…”
Section: Introductionmentioning
confidence: 99%
“…They extend across ecological timescales, from the cycles of the tides (Gibson 2003;Krumme 2009) to those of the seasons (Hyndes et al 1999;Milligan et al 2020) and those exhibited over ontogenetic development (Grubbs 2010;Frank et al 2018). They are also prevalent across trophic levels, from the diel vertical migration (DVM) of plankton (Hays 2003;Bianchi and Mislan 2016) to the diving patterns of cetaceans (Keen et al 2019;Caruso et al 2020) and pelagic sharks (Papastamatiou and Lowe 2012;Schlaff et al 2014). An important area of research in marine ecology is to understand the drivers of these trends.…”
Section: Introductionmentioning
confidence: 99%
“…In this volume, Caruso et al . (2021) used non‐invasive digital acoustic recording tags (D‐Tags) to study the dive behavior of 28 blue whales in the northern Chilean Patagonia. Their results showed that Chilean blue whales dove to significantly greater depths during the day compared to night‐time, when most time was spent close to the surface.…”
Section: Applications Of Useful Methodsmentioning
confidence: 99%
“…In recent decades, biologging technology has become increasingly applicable, which allows researchers to take different types of measurements, such as GPS location, speed, and/or physiological parameters of animal, and depth, temperature, or salinity of environment (McIntyre 2014). In this volume, Caruso et al (2021) used non-invasive digital acoustic recording tags (D-Tags) to study the dive behavior of 28 blue whales in the northern Chilean Patagonia. Their results showed that Chilean blue whales dove to significantly greater depths during the day compared to night-time, when most time was spent close to the surface.…”
Section: Biologgingmentioning
confidence: 99%
“…whether a species is nocturnal or diurnal) and seasonal (e.g. whether an individual is breeding or moulting) patterns can modulate sensitivity to disturbance, the severity of response, and the likelihood of exposure (Caruso et al, 2020 ). Some fish species have been observed to respond more strongly to disturbance at night (Neo et al, 2018 ).…”
Section: Receptormentioning
confidence: 99%